Kajian Optimasi Produksi dan Strategi Pengembangan Usaha Produk Fish Jelly (Studi Kasus pada PT “XP” di Jakarta) - - Ismarsudi; Ani Suryani; Darwin Kadarisman (MANAJEMEN IKM: Jurnal Manajemen Pengembangan Industri Kecil Menengah, 2011)
PT “XP” in its bussiness production has produced Fish Jelly  with five types of products, there are Fish Sausage, Fish Ball, Fish Kakinaga, “Otak–otak” and Fish Finger.The main raw material that being used by PT XP for those products are surimi, fatty tuna and other fish. Some of the constraints in marketing development for Fish and Fishery products in this country are supply and demand aspect. The former constraint includes quantity and continuity, quality, selling price, definite variety of products, weak market information,  limited facilities and marketing infrastructure and not conducive business climate. Demand aspect includes low level of fish consumption, dynamic consumer preferences, weak marketing, distribution network and market strategy. Analysis method that being used in this study is Exponential Comparative Method (MPE). It’s one of the methods to get superior products. Net profit margin reflects management's ability to generate net income. Linear Programming (LP) to achieve a single goal such as maximizing profits or minimizing cost. Other analysis, SWOT (strengths, weaknesses, opportunities and threats), Matriks External Factor Evaluation (EFE) and Internal Factor Evaluation (IFE) are used to analyze external and internal factors. Results of the studies obtained, the superior first product of fish finger and second product fish ball.  The maximum profits that obtained from LP Calculation is Rp 31.800/kg or Rp 31.800.000/ton, with production composition 25% fish finger dan 75% bakso ikan for favored products. PT “XP” has opportunity in fish jelly production since it has permanent distributor of raw materials, and yet has threat that is production cost increase caused by raised fuel prices and electricity fare. This company’s main strength lays on the manager’s preseverance in managing this business, while the Main Weakness of this company that is lack of capital to get supplies. The result evaluation on external and internal factor (EFE and IFE) to make the company in a quadrant agresif position, that company in a good posisition to develop the business. The company can use the internal power for: (1) make use the external opportunity; (2) to content with internal weakness; and (3) avoid the extend threats.